2017
DOI: 10.11138/mltj/2017.7.1.001
|View full text |Cite
|
Sign up to set email alerts
|

I.S.Mu.L.T. first-time patellar dislocation guidelines

Abstract: SummaryPrimary traumatic patellar dislocation is common, particularly in young active individuals. A consensus on its management is still lacking. The present work provides easily accessible guidelines to be considered as recommendations for a good clinical practice developed through a process of systematic review of the literature and expert opinion, to improve the quality of care and rationalize the use of resources. Level of evidence: Ia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 113 publications
0
31
0
Order By: Relevance
“…33 Despite reports of reduced recurrence rates after surgical management, nonoperative management remains the mainstay of treatment. 24,33,34 However, in a patient with a high risk of recurrence, surgery may be considered the preferred management option. 18 It would therefore be helpful to know which factors were most associated with an increased risk of recurrence.…”
mentioning
confidence: 99%
“…33 Despite reports of reduced recurrence rates after surgical management, nonoperative management remains the mainstay of treatment. 24,33,34 However, in a patient with a high risk of recurrence, surgery may be considered the preferred management option. 18 It would therefore be helpful to know which factors were most associated with an increased risk of recurrence.…”
mentioning
confidence: 99%
“…Lateral patellar dislocations comprise 2% to 3% of acute knee injuries. 1 Various anatomic and patient factors predispose individuals to these injuries. These factors include generalized ligamentous laxity, as found in Ehlers-Danlos syndrome, as well as “miserable malalignment syndrome,” which is a combination of femoral anteversion, genu valgum, and external tibial torsion or pronated feet that leads to an increased Q-angle.…”
mentioning
confidence: 99%
“… 2 , 3 Patellar dislocations commonly occur during athletic activity, and over 90% are indirect injuries occurring through a valgus and torsional force on a flexed knee. 1 All acute patellar dislocations result in increased laxity of the medial patellofemoral ligament (MPFL), with 50% to 96% of post-dislocation patients having complete deficiency of the ligament during surgical exploration. 4 , 5 …”
mentioning
confidence: 99%
“…I am not sure whether all these indications were initially conceived by the initiator, but the fact stands that biomechanical and clinical studies have demonstrated a high degree of patients' satisfaction, and low complication rates, and marked improvement in patientreported outcome measures. 4 Part and parcel of modern life is the high level of physical activity that may cause musculoskeletal ailments, but which we nevertheless wish to maintain for as long as possible. The present work is a careful retrospective review of a selected group of patients with pain and patellofemoral arthritis who underwent the procedure, and in whom especially the return to sport dimension was focused on.…”
Section: See Related Article On Page 1022mentioning
confidence: 99%